EFEKTIFITAS WAKTU PEMBERIAN DAN KONSENTRASI PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN HASIL KENTANG (SOLANUM TUBEROSUM L.) VARIETAS SUPEJOHN - Sambeka, Frangki; Runtunuwu, Semuel D.; Rogi, Johannes E.X. (Universitas Sam Ratulangi, 2012)
ABSTRACT The study aimed to examine the influence of time of application and concentration of paclobutrazol on growth and yield of potato crop Supejohn held in District Modoinding South Minahasa regency, from March to June 2012, using a randomized block design with two factors. The first factor is the concentration of Paclobutrazol with four standards are: 0 ppm, 75 ppm, 100 ppm, 125 ppm and the second factor is the provision of a three-level applications MST 4, 5 and 6 MST MST (Week After Planting). Based on research, the results of analysis of variance showed an interaction between application timing and concentration of paclobutrazol. Combination treatment with 125 ppm paclobutrazol 6 WAP application time can give significant effect on plant height, number of chlorophyll content, percentage weight class tuber yield components in the form of increased crop production amounted to 45.04 kg / plot (24 plants) / range 52. ton / ha by pressing the vegetative growth of plants. Key words : Supejohn, time application, concentration, paclobutrazol